1969
DOI: 10.1090/s0025-5718-1969-0239732-8
|View full text |Cite
|
Sign up to set email alerts
|

On the series expansion method for computing incomplete elliptic integrals of the first and second kinds

Abstract: Abstract. In the present paper an attempt is made to improve the series expansion method for computing the incomplete integrals F(0, k) and 77(0, k). Therefore the following three pairs of series covering the region -l5Sfc^l,O^0< ir/2 are used: series obtained by a straightforward binomial expansion of the integrands, series valid for k'2 tan2 0 < 1, and new series which converge for 0 > tt/4 and for all values of k. Terms of the last two pairs of series can be generated by means of the same recurrence relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…The series expansions of R F and R D using u 14c , v 14c , and a 14c are essentially the same as the third series expansion of F (ϕ|m) and E(ϕ|m) given in [38]. It is interesting to see that e 5c , e 14c , and e 15c do not depend on y nor on m. This was already pointed out for e 14c in [38].…”
Section: Special Addition Formulassupporting
confidence: 69%
See 2 more Smart Citations
“…The series expansions of R F and R D using u 14c , v 14c , and a 14c are essentially the same as the third series expansion of F (ϕ|m) and E(ϕ|m) given in [38]. It is interesting to see that e 5c , e 14c , and e 15c do not depend on y nor on m. This was already pointed out for e 14c in [38].…”
Section: Special Addition Formulassupporting
confidence: 69%
“…The series expansions of the classic elliptic integrals have been discussed mainly in order to seek a convenient way to evaluate them by means of the elementary functions such as the logarithm or inverse trigonometric functions [18,21,27,19,32,38,33,2,34]. Nevertheless, these methods are known to be slower than: the standard methods utilizing Landen and/or Gauss transformations [3,4,5,6,26,36].…”
Section: Existing Researches On Series Expansions Of Elliptic Integralsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows calculating the detachment work, in small particle to droplet size ratio limit as the area of the triangle on the displacementforce diagram. Using Eqs (70) and (71) we can write for the case of the 90 • contact angle:…”
Section: Work Of Detachmentmentioning
confidence: 99%
“…The present study is suggested by analogous work for power series developments of the first two kinds of elliptic integrals. In this connection, see the recent study by Van de Vel [3] and the references quoted there. For convenience and completeness, we also give the representations previously found.…”
mentioning
confidence: 94%